"Menyokong Kesehatan dan Kesejahteraan: Pendekatan Manajemen Perusahaan terhadap Penyuluhan Karyawan" : Studi Kasus pada Industri (RS UMMI) - Moedigdo Sigit Prakoso , Moedigdo Sigit Prakoso (Cakrawala Akuntansi & Manajemen, 2024)
This study aims to investigate the company's management approach in supporting employee health and wellbeing through an extension programme in Industry (UMMI Hospital). This approach was taken to enhance employees' understanding of the importance of health and wellbeing in the work environment. By adopting a qualitative method, data was collected through in-depth interviews with HR managers, medical staff, and selected employees at RS UMMI. The study findings highlighted the company's management strategy in designing and implementing an effective extension programme, including topics such as healthy lifestyle, stress management, and the importance of a balanced diet. The study also evaluated the impact of the extension programme on employees' health and well-being as well as organisational culture at UMMI Hospital. The results of this study are expected to provide valuable insights for other companies looking to implement similar programmes to improve employee well-being and overall organisational productivity.